Possible use of Punica granatum (Pomegranate) in cancer therapy - Khwairakpam, A.; Bordoloi, D.; Thakur, K.; Monisha, J.; Arfuso, Frank; Sethi, G.; Mishra, S.; Kumar, Alan Prem; Kunnumakkara, A. (Academic Press, 2018)
The intake of fruits has proven to reduce the risk and incidence of cancer worldwide and plays a crucial role in cancer prevention. Pomegranate (Punica granatum), which belongs to the Punicaceae family, is one such plant that contains beneficial nutrients as well as many bioactive components and important phytochemicals that can be attributed to cancer-related therapeutic purposes. Pomegranate possesses antioxidant, anti-inflammatory, anti-proliferative, anti-angiogenic, anti-invasive, and anti-metastatic properties, and induces apoptosis. It also down-regulates various signaling pathways such as NF-?B, PI3K/AKT/mTOR, and Wnt, and down-regulates the expression of genes that are responsible in cancer development, such as anti-apoptotic genes, MMPs, VEGF, c-met, cyclins, Cdks, and pro-inflammatory cytokines. Therefore, inclusion of the fruit in one's diet would assist in a healthy life protected from cancer and also act as an effective chemotherapeutic with no toxic side effects.